Benign and malignant thyroid nodules with autoimmune thyroiditis - Georgia N. Kassi; Catherine C. Evangelopoulou; Konstantinos D. Papapostolou; Helen J. Karga (Archives of Endocrinology and Metabolism, 2022)
ABSTRACT Objective: The prevalence of autoimmune thyroiditis (AT) in papillary thyroid carcinoma (PTC) is still controversial. The aim of this study was to investigate the frequency of coexistence of PTC with AT versus that of the coexistence of benign nodules with AT. Materials and methods: This was a cross-sectional retrospective study including patients operated on for thyroid nodules from January 2011, to April 2021. The frequency of papillary carcinomas cooccurring with AT was compared to that of benign nodules cooccurring with AT, which was assessed based on cytopathological diagnosis after thyroidectomy. Results: The study included 668 cases of benign nodules and 420 cases with PTC. No statistically significant difference was observed between cases of benign and PTC nodules regarding the presence of AT (25% vs. 28%, respectively, p = 0.177). The size of the PTC compared to that of the benign predominant nodules was significantly smaller both in the absence (0.96 ± 1.09 cm vs. 2.19 ± 1.06 cm, p < 0.05) and in the presence (0.77 ± 0.76 cm vs. 1.67 ± 1.08 cm, p < 0.01) of AT. In the binary logistic regression analysis of the PTC, the only variable associated with AT was multifocality (odds ratio: 1.750, 95% confidence intervals: 1.131-2.706, p = 0.013). The incidences of lymph node involvement and advanced stage PTC were very low both in the presence and absence of AT. Conclusion: The nodules present with PTC were not more likely to coexist with AT than benign nodules were. The small incidence of advanced PTC indicates a significant improvement in early-stage diagnosis.